2014
DOI: 10.1002/jcla.21702
|View full text |Cite|
|
Sign up to set email alerts
|

Detection and Assessment of Clarithromycin Inducible Resistant Strains Among Korean Mycobacterium abscessus Clinical Strains: PCR Methods

Abstract: Background: Mycobacterium abscessus group belongs to a group of rapidly growing mycobacteria (RGM) and, following Mycobacterium avium complex, is the second most common pathogen responsible for lung disease caused by nontuberculous mycobacteria (NTM). Clarithromycin is known to be the key drug in the treatment of M. abscessus group disease, but a high failure rate of treatment response is reported due to clarithromycin inducible resistance. Methods: Using the results from a clarithromycin susceptibility test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
3
11
2
Order By: Relevance
“…massiliense in our isolates, which appears to be more susceptible to macrolides than M. abscessus sensu stricto and M. bolletii [34]. This contrasts with previous studies describing constitutive macrolide resistance between 2.7% and 28.6% and inducible resistance in 65% to 68.8% of M. abscessus complex isolates [35–37]. …”
Section: Discussioncontrasting
confidence: 98%
“…massiliense in our isolates, which appears to be more susceptible to macrolides than M. abscessus sensu stricto and M. bolletii [34]. This contrasts with previous studies describing constitutive macrolide resistance between 2.7% and 28.6% and inducible resistance in 65% to 68.8% of M. abscessus complex isolates [35–37]. …”
Section: Discussioncontrasting
confidence: 98%
“…abscessus with the macrolide-susceptible erm(41) C28 sequevar but also in M. abscessus subsp. abscessus with the intrinsically macrolide-resistant erm(41) T28 sequevar (15,18,19,30,31). In our study, of the 13 isolates with rrl mutations, 85% had the T28 sequevar and 15% had the C28 sequevar of erm(41).…”
Section: Discussionmentioning
confidence: 46%
“…8006) harboring a point mutation 2059A>G in the rrl gene showed resistance to clarithromycin from day 3 through day 14 (MIC > 128 µg/ml). The presence of rrl mutations was reported in up to 30% of newly isolated strains in East Asia (16,35), whereas no rrl mutations were identified at the time of diagnosis in Spain (36). It has been reported that mutations in the rrl gene rapidly accumulate following clarithromycin use in monotherapy (3).…”
Section: Discussionmentioning
confidence: 99%